Enfermedades psicosomáticas en neumología - Morales Miranda, Carmen (2000)
The psychosomatic discipline is dedicated to the study of the interrelationship between the mind, the psyche, and the body, and offers an answer to the questions: How do the mental, and psychic processes are the focus of study or in which form the physical processes are manifested at a mental or psychic level?